Five days gone : the mystery of my mother's disappearance as a child - Cumming, Laura (Scribner, an imprint of Simon & Schuster, 2019)
"In the fall of 1929, when Laura Cummings mother was three years old, she was kidnapped from a beach on the Lincolnshire coast of England. There were no screams when she was taken, suggesting the culprit was someone familiar to her, and when she turned up again in a nearby village several days later, she was found in perfect health and happiness. No one was ever accused of a crime. The incident quickly faded from her memory, and her parents never discussed it. To the contrary, they deliberately hid it from her, and she did not learn of it for half a century. This was not the only secret her parents kept from her. For many years, while raising her in draconian isolation and protectiveness, they also hid the fact that she'd been adopted, and that shortly after the kidnapping, her name was changed from Grace to Betty. In Five Days Gone, Laura Cumming brilliantly unspools the tale of her mother's life and unravels the multiple mysteries at its core. Using photographs from the time, historical documents, and works of art, Cumming investigates this case of stolen identity with the toolset of a detective and the unique intimacy of a daughter trying to understand her family's past and its legacies. Compulsive, vivid, and profoundly touching, Five Days Gone is a masterful blend of memoir and history, an extraordinary personal narrative unlike any other."--Amazon